Poor Natural Resource Utilization as the Bane of Industrialization in Nigeria: Evidence from National Bureau of Statistics Petrol Price Watch - Jonathan E. Ogbuabor; Anthony Orji; Charles O. Manasseh; Cynthia A. Nwosu (International Journal of Economics and Financial Issues, 2018)
Industrializing Nigeria requires steady and affordable energy supply and distribution. Hence, this paper examined Nigeria’s petrol market for evidence of consumers paying above the government approved prices and for evidence of asymmetric response of retail petrol prices to changes in oil price. National Bureau of Statistics’ (NBS) Petrol Price Watch data was used together with descriptive analysis and an ARDL-ECM model. Overall, we find that even when the product is subsidized, consumers in most states pay above the government approved prices. In addition, we find that both in the short-run and long-run, retail petrol prices in Nigeria respond asymmetrically to changes in oil price. These findings are contrary to Nigeria’s status as an oil-rich country, thereby capturing the stark reality of poor utilization of the country’s oil resources to improve its industrial competitiveness. Keywords: Natural resource; Petrol pricing; Industrialization; Nigeria JEL Classifications: Q31; R32; L11; N17